THE INTER-LEARNING OF GEOMETRY IN MIDDLE ELEMENTARY EDUCATION STUDENTS IN ECUADOR - Erreyes, Helder Marcell Barrera; Jiménez, Jaqueline Alexandra Vaca; Erreyes, Jenny Cecilia Barrera; Flores, Jorge Francisco Abril; García, Teresa Marlene Barragán (International Journal of Research -GRANTHAALAYAH, 2018)
One of the main problems that in Ecuadorian education makes reference to the shortcomings in the quality of learning mathematics, specifically to the development of cognitive skills, thus overlooking motor skills and affective elements, in other words, there is not integral learning for life. Therefore, the aim is to diagnose the level of inter-learning, establishing a suitable strategy that is in line with performance-based skills for each period in geometry, methods and curriculum adaptations as well as apply the didactics for inter-learning in geometry with middle school students. In order to offer a series of applicable and practical tools that optimize the development of integral skills in students, specifically in topic-based work in geometry, the inductive method has been used because it adapts to the required needs in both the researching process and the structuring of the proposed strategy. While collecting data, it was possible to confirm that the contents of geometry are not applicable in practical life since they are taught theoretically. Moreover, it was detected that teachers have a need for alternative strategies which help them improve the quality of teaching. To conclude, with the appropriate use of teaching strategies, learning is made easier in geometry contents.